A Robust Pipeline for the Multi‐Stage Accelerated Differentiation of Functional 3D Cortical Organoids from Human Pluripotent Stem Cells. Issue 1 (12th January 2023) - Whye, Dosh; Wood, Delaney; Saber, Wardiya Afshar; Norabuena, Erika M.; Makhortova, Nina R.; Sahin, Mustafa; Buttermore, Elizabeth D.
Abstract: Disordered cellular development, abnormal neuroanatomical formations, and dysfunction of neuronal circuitry are among the pathological manifestations of cortical regions in the brain that are often implicated in complex neurodevelopmental disorders. With the advancement of stem cell methodologies such as cerebral organoid generation, it is possible to study these processes in vitro using 3D cellular platforms that mirror key developmental stages occurring throughout embryonic neurogenesis. Patterning‐based stem cell models of directed neuronal development offer one approach to accomplish this, but these protocols often require protracted periods of cell culture to generate diverse cell types and current methods are plagued by a lack of specificity, reproducibility, and temporal control over cell derivation. Although ectopic expression of transcription factors offers another avenue to rapidly generate neurons, this process of direct lineage conversion bypasses critical junctures of neurodevelopment during which disease‐relevant manifestations may occur. Here, we present a directed differentiation approach for generating human pluripotent stem cell (hPSC)‐derived cortical organoids with accelerated lineage specification to generate functionally mature cortical neurons in a shorter timeline than previously established protocols. This novel protocol provides precise guidance for the specification of neuronal cell type identity as well as temporal control over the pace at which cortical lineage trajectories are established. Furthermore, we present assays that can be used as tools to interrogate stage‐specific developmental signaling mechanisms. By recapitulating major components of embryonic neurogenesis, this protocol allows for improved in vitro modeling of cortical development while providing a platform that can be utilized to uncover disease‐specific mechanisms of disordered development at various stages across the differentiation timeline. © 2023 Wiley Periodicals LLC. Basic Protocol 1 : 3D hPSC neural induction Support Protocol 1 : Neural rosette formation assay Support Protocol 2 : Neurosphere generation Support Protocol 3 : Enzymatic dissociation, NSC expansion, and cryopreservation Basic Protocol 2 : 3D neural progenitor expansion Basic Protocol 3 : 3D accelerated cortical lineage patterning and terminal differentiation